2020
DOI: 10.21468/scipostphys.9.4.051
|View full text |Cite
|
Sign up to set email alerts
|

Modulation induced transport signatures in correlated electron waveguides

Abstract: Recent transport experiments in spatially modulated quasi-1D structures created on top of LaAlO_33/SrTiO_33 interfaces have revealed some interesting features, including phenomena conspicuously absent without the modulation. In this work, we focus on two of these remarkable features and provide theoretical analysis allowing their interpretation. The first one is the appearance of two-terminal conductance plateaus at rational fractions of e^2/he2/h. We explain how this phenomenon, previously believed to be poss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…Note also that the findings presented below remain qualitatively the same for other choices of scaling. Finally, in the case of SOC produced via modulations, it would be reasonable to consider a modulated interaction as in [47], where it has been shown that such assumption can produce fractional conductance plateaux, compatible with the experimental data presented in [22,23].…”
Section: B Electron-electron Interactionssupporting
confidence: 67%
“…Note also that the findings presented below remain qualitatively the same for other choices of scaling. Finally, in the case of SOC produced via modulations, it would be reasonable to consider a modulated interaction as in [47], where it has been shown that such assumption can produce fractional conductance plateaux, compatible with the experimental data presented in [22,23].…”
Section: B Electron-electron Interactionssupporting
confidence: 67%
“…We also checked that the findings presented below remain qualitatively the same for other choices of scaling. Finally, in the case of SOC produced via modulations, it would be reasonable to consider a modulated interaction as in [48], where it has been shown that such assumption can produce fractional conductance plateaux, compatible with the experimental data presented in [22,23]. Note that our model for the interactions is not a BCS model for superconductivity [49,50], but instead a model to describe electron pairing without superconductivity.…”
Section: B Electron-electron Interactionssupporting
confidence: 57%
“…2a, which suggests that it is the basis of the behavior observed in the experiments. This single-particle Kronig-Penney model cannot predict the full fractional conductance plateaus, which are understood to require the presence of strong electron-electron interactions [29,30,31].…”
Section: Shavit Et Al Have Considered a Theoretical Frameworkmentioning
confidence: 99%
“…[29,30] in which fractional conductances arise in multichannel 1D quantum wires due to high order back-scattering processes. Such fractional conductances were shown to require strong repulsive electron-electron interactions to be observed, but a recent theory suggests that this could also be the case for strong attractive modulated interactions [31]. For the simplest high-order scattering process involving three particles, this theory predicts a plateau at 1.8e 2 /h which can become gap-protected for strong modulated interactions.…”
mentioning
confidence: 99%